2004
DOI: 10.1002/app.20854
|View full text |Cite
|
Sign up to set email alerts
|

Structural and conformational changes in solid‐phase chlorinated polyethylene

Abstract: ABSTRACT:The structural and conformational changes in solid-phase chlorinated polyethylene samples of different average molecular masses were studied with infrared spectroscopy. Characteristic absorption bands for both chlorinated polyethylene and chlorinated high-molecular-mass polyethylene, containing 1-56% Cl, were identified. The chlorine content in the macromolecular chains, ranging from 1 to 15%, was associated with the presence of single chloromethylene groups and short syndiotactic structural sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…From the variation of the spectra with increasing T c , it is obvious that the absorbance of the TT band (612 cm −1 ) decreases dramatically at T c > 53 °C, indicating that as form II is enabled, the content of gauche conformers around the substitution increases substantially in a narrow T c transition range. Hence, although a similar change in conformation was noticed in a small extent in EVC copolymers, 25 the precise nature of the Cl substitution in PE15Cl induces at T c > 53 °C macromolecular packing characterized by a very high concentration of TG bonds adjacent to the CH−Cl unit.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…From the variation of the spectra with increasing T c , it is obvious that the absorbance of the TT band (612 cm −1 ) decreases dramatically at T c > 53 °C, indicating that as form II is enabled, the content of gauche conformers around the substitution increases substantially in a narrow T c transition range. Hence, although a similar change in conformation was noticed in a small extent in EVC copolymers, 25 the precise nature of the Cl substitution in PE15Cl induces at T c > 53 °C macromolecular packing characterized by a very high concentration of TG bonds adjacent to the CH−Cl unit.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…Spectra of EVC in this stretching region are complex due to the presence of diads, vicinal, and other mixed substitutions in addition to the isolated one, thus increasing the number of conformations around the C−CHCl unit. 21,25 Only for EVC with a relatively low (<6 mol %) content of Cl is the average backbone distance between Cl sufficiently long to have the C−Cl stretch unaffected by nearby −CHCl units, as indicated by two absorbances at 612 and 665 cm −1 instead of multiple or broad bands. 21,25 It was also shown that with increasing processing temperature random ethylene−vinyl chloride copolymers adopt slightly higher concentrations of TG(GT) conformers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations